PENGALOKASIAN GAS LPG 3 KG TERBANYAK KE PANGKALAN MITRA PT. PUTRA PALUTA ASAHAN DENGAN WEIGHT PRODUCT - Enda Triswati; Nur Wati; Wan Mariatul Kifti (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
LPG in the community is one of the economical needs in the household. The increasing use of LPG is now a concern of many circles because it is a product that is very much needed by consumers. However, the problem that exists is that the process of allocating 3 Kg LPG gas by PT. Putra Paluta Asahan has not been carried out objectively. Therefore, a decision support system is needed to help the selection process for the bases to be carried out efficiently and systematically. From several methods in the decision support system, this Weighted Product was chosen to be applied to the system. The purpose of this study was to assist in the process of allocating 3 Kg LPG gas to Pangkalan according to predetermined criteria. The decision support system made is able to provide references in the decision-making process in an objective, effective and efficient manner. This study provides fairly accurate results where the allocation process is right on target with data obtained from PT. Putra Paluta Asahan.